Teaching Radio Telemetry using Microcontrollers with Low Power Radio Devices. (13th May 2015) - Ibrahim, Dogan; Sadikoglu, Fahreddin
Abstract: Radio telemetry is used in many remote monitoring and remote control applications, such as in environmental monitoring, pollution monitoring, weather forecasting, and other applications. In typical applications sensors are used to collect data and this data is then transmitted to a remote receiving station where it is analysed. This paper outlines the basic principles of the radio telemetry systems and gives an example to show how such a system can be designed and used in teaching the principles of radio telemetry. The designed system is based on a popular microcontroller.